Studi Bahaya Antropogenik yang Disebabkan Pembuangan Sampah di Bentuklahan Fluvio-Marin di Sebagian Muara Angke, Jakarta Menggunakan Data Penginderaan Jauh Udara - Nurwita Mustika Sari; Mangapul Parlindungan Tambunan (Diponegoro University, 2021)
Anthropogenic hazards are hazards arising from human actions or negligences. Anthropogenic hazards can affect both human and the broader ecosystem and various landforms. Waste as the effect of human activity is a big problem in urban areas related to the difficulty of waste management while waste production continues to increase. The impact of poor waste management in the city is a potential anthropogenic hazard for the region. Part of the city that often receives less attention related to waste or environmental sanitation and has been negatively affected by waste is the coastal area in a big city, which is kind of fluvio-marine landform unit, one of which is Muara Angke, which is the study area of this research. Identification of the waste disposal site is carried out to determine the level of anthropogenic hazard posed by waste in the area. With very high spatial resolution obtained by aerial remote sensing data, identification of objects in urban areas such as waste disposal site can be conducted. The purpose of this study is to identify the waste disposal site in part of Muara Angke region and to identify the potential of anthropogenic hazard caused by waste in the area. The data used is the LSU (LAPAN Surveillance UAV) camera data. The method proposed in this research is visual interpretation LSU camera data. The result showed that waste disposal location can be performed using aerial remote sensing data and visual interpretation to the data.